Strategies for Improving 21st Century Competencies in Secondary Schools in Indonesia: A Systematic Literature Review - Hilmiatussad, Kinanti Geminastiti; Ahman, Eeng; Disman, Disman; Dahlan, Dadang (Jurnal Pendidikan Progresif, 2024)
Objective: This study aims to evaluate strategies to improve 21st century competencies in secondary schools in Indonesia with a focus on the implementation of learning curricula and digital literacy mastery. 21st century competencies include critical thinking, creative, communication, collaboration, character development and citizenship skills. This study will answer research questions related to what research results are found in reference articles regarding strategies to improve 21st century competencies of secondary school students in Indonesia, what factors influence the improvement of 21st century competencies of secondary school students in Indonesia, and how policies related to strategies to improve 21st century competencies of secondary school students in Indonesia. Methods: Systematic Literature Review (SLR) with PRISMA approach is the method used in this research, through identification, screening, eligibility and inclusion stages to analyse 42 relevant articles from 2017-2024 sourced from Google Scholar. Findings: The results show three main factors that influence the improvement of students‘ competence: teachers’ competence, curriculum innovation and learning methods, and the role of digital technology. Teacher competence in digital literacy is the key to successful technology-based learning. Flexible, adaptive and digitisation-based curriculum innovations can encourage mastery of 21st century competencies, especially through innovative learning methods such as blended learning and project-based learning. In addition, digital technology plays an important role in facilitating interactive and effective learning, although uneven infrastructure remains a challenge in Indonesia. Conclusion: This study suggests the integration of digital literacy in the curriculum, the improvement of teachers' competence through continuous training, as well as the development of technology infrastructure in schools. Education policies that support curriculum flexibility and technology adoption are believed to improve students' readiness to face global challenges. This study provides strategic recommendations for educators, policy makers and educational institutions in designing learning systems that are relevant to the digital era. Keywords: curriculum, digital literacy, 21st century competencies.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024130